En mærkelig forbindelse? Det tidlige vesttysk-danske efterretningssamarbejde - Friis, Thomas Wegener; Schmidt-Eenboom, Erich (Fra Krig og Fred, 2026)
The relations between intelligence services are a normal part of international relations. Nevertheless, it is a history which is rarely told. An important reason for this is that some intelligence services consequently deny declassification of files relating to this field. 6us, the history of the early relations between the Org. Gehlen/the Bundesnachrichtendienst (FE) and Danish Military Intelligence officers a rare glimpse behind the scenes at a dynamic period of time. After the end of the Second World War, the Danish Military Intelligence was eager to reach out to their former foes. In their search for the possible future German intelligence and military elites, the question of these men’s’ political track record was not a major priority. In early 1948, it resulted in an agreement between the Danes and the CIA-sponsored General Reinhard Gehlen. 6is understanding paved the way for a cooperation which both sides seemed to appreciate. 6e Danes exchanged both intelligence analysis, raw intelligence, and eventually also the identity of sources behind the iron curtain with their German partners. Also, the Danish officers were willing to facilitate German intelligence operations in the Baltics as long as Danish politicians were not consulted. From 1962, the BND was granted the rights to an intelligence station at the embassy in Copenhagen. The Germans on their side appeared to be a respectful, bigger partner, willing to share expertise and resources with the smaller Danish allies, and to support Danish Stay Behind activities in Northern Germany. Furthermore, the BND readily helped their Danish colleagues with a no-disclosure agreement which sought to aid the Danish Military intelligence service in regaining the control of the flow of information to their political superiors. Finally, the transcripts of the meetings between leading Danish and German intelligence officer allow insights to Danish intelligence relations to the US, the UK, and France as well as to Danish HUMINT operations in the in the Early Cold War.